The Effects of the Trans-Regional Transport of PM2.5 on a Heavy Haze Event in the Pearl River Delta in January 2015 - Qing Chen (Atmosphere, 2019)
The Pearl River Delta (PRD), a region with the fastest economic development and urbanization in China, sometimes has severe haze pollution caused by fine particulate matter (PM2.5). From October to April of the following year, the PRD is influenced by northerly winds, which can bring pollutants from upwind polluted regions. However, the ways that pollutants are transmitted and the contributions of trans-regional inputs are not yet clear. Observational analysis and numerical simulations are applied to explore the effect of PM2.5 trans-regional transport during a heavy haze event occurring from 14 to 25 January 2015. The results show that northerly winds resulted in an increase in the PM2.5 concentration in the northern PRD one day earlier than in the southern PRD. The main transport path of PM2.5 was located at an altitude of 0.1 to 0.7 km; the maximum total transport intensity below 3 km was 9.7 × 103 μg·m−2·s−1; and the near-surface concentration increased by 13.7 to 34.4 μg/m3 by trans-regional transport, which accounted for 56.5% of the contribution rate on average. Southerly winds could also bring a polluted air mass from the sea to the coast, causing more severe haze in coastal regions blocked by mountains, although the overall effect is reduced pollution.